ANALISIS PENGARUH TOTAL ASET TERHADAP PROPORSI PENDAPATAN OPERASIONAL SELAIN BUNGA DENGAN LDR (LOAN TO DEPOSIT RATIO) SEBAGAI VARIABEL MODERATING PADA INDUSTRI PERBANKAN DI INDONESIA - Mega Sukmawati; Muchlis . (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
This study aims to determine the effect of Total Assets of the proportion of Non-Interest Operating Income with the Loan to Deposit Ratio (LDR) as a moderating variable in the banking industry in Indonesia which is expected to be useful for the banking sector in Indonesia as inputs in order to increase the income of banks in Indonesia and is expected to create new policies in the banking world in its operations so as to increase the income of banks in Indonesia. This research is a causal research that aims to test hypotheses about the influence of independent variables on the dependent variable with quantitative descriptive approach. After going through the screening of the outlier sample in this study was a conventional bank whose financial statements published by Bank Indonesia in the years 2009-2013 as many as 106 banks. The test equipment used is the analysis of multiple regression analysis. The results showed that in testing hypotheses about the effect of total assets to the proportion of non-interest operating income obtained tcount > ttable is 4,844 > 1,983 so the variable total assets significantly influence the proportion of non-interest operating income in the banking industry in Indonesia amounted to 18.4%. Simultaneously there is significant influence between the total assets, the Loan to Deposit Ratio (LDR) and the interaction between total assets and LDR to the proportion of non-interest operating income amounted to 27.5%. and Loan to Deposit Ratio (LDR) affect the size of the effect of total assets to the proportion of non-interest operating income in the banking industry in Indonesia with large influence is 57.68%. Keywords : Total Assets, Proportion of Non-Interest Operating Income, Loan to Deposit Ratio (LDR).